Fatores de influência na captação de recursos financeiros para startups em campanhas de equity crowdfunding - Pazini, Gustavo André (My University, 2021)
Entrepreneurial finance can be a necessity when the company is in an initial stage and needs to grow and consolidate itself in the market. In this context, Equity Crowdfunding is a type of financing that allows the general public to invest in startups that have businesses that align with their interests. Thus, the objective of this research is to analyze how certain influencing factors act on Equity Crowdfunding used in the financial promotion of startups, enabling successful fundraising and aiming at the growth of this type of company. To this end, a qualitative exploratory study was developed, which included eight interviews with involved stakeholders. The excerpts from the interviews made it possible to analyze how the factors addressed act in Equity Crowdfunding, both positively and negatively. The exposed has a direct impact on the results of the campaigns that aim to raise financial resources for startups, enabling the growth of this type of company and its consolidation in the market [resumo fornecido pelo autor].
O financiamento de empreendimentos pode ser uma necessidade quando a empresa está em estágio inicial e precisa crescer e se consolidar no mercado. Nesse contexto, o Equity Crowdfunding é uma modalidade de financiamento que possibilita, ao público em geral, investir em startups que possuam negócios que se alinhem aos seus interesses. Assim, o objetivo desta pesquisa é analisar como determinados fatores de influência atuam sobre o Equity Crowdfunding utilizado no fomento financeiro de startups, possibilitando captações de recursos bem-sucedidas e visando o crescimento desse tipo de empresa. Para tanto, foi desenvolvido um estudo qualitativo exploratório, que contou com a realização de oito entrevistas com os stakeholders envolvidos. Os excertos das entrevistas possibilitaram analisar como os fatores abordados atuam no Equity Crowdfunding, tanto de forma positiva, como negativa. O exposto gera um impacto direto no resultado das campanhas que têm por objetivo captar recursos financeiros para as startups, possibilitando o crescimento desse tipo de empresa e a sua consolidação no mercado [resumo fornecido pelo autor].
Keywords: Financiamento coletivo; Negócios; Empresas; Crowd funding; Business; Business enterprises